Suitability of azolla(azolla pinnata) for biogas slurry enrichment - Bishnu Prasad Paudel (Department of Soil science and Agricultural chemistry,College of Horticulture, 2012)
A study on “Suitability of azolla (Azolla pinnata) for biogas slurry enrichment” was conducted during 2010-11 at College of Horticulture, Vellanikkara to evaluate the optimum ratio of cow dung and azolla for biogas slurry enrichment, to identify the best material to prepare quality organic manure from the enriched slurry and also to adjudge the crop response to enriched organic manure. To attain the objectives, three separate experiments were conducted in a phased manner.